Studi Kebijakan Mengenai Gerakan Literasi Sekolah - Zuliyatur Rochmah; M. Yunus Abu Bakar (Asatiza: Jurnal Pendidikan, 2021)
The purpose of this research was to find out the policy on the issuance of the Minister of Education and Culture Regulation on the development of character against the background of Indonesia's literacy level, which is ranked 64th out of 72 countries. The school literacy movement is an effort that is carried out comprehensively and continuously to make schools a learning organization whose citizens are literate throughout life through public involvement. The qualitative approach was designed for this study. The analysis showed that Starting from the existence of Permendikbud Number 23 of 2015, which is the basis of the School Literacy Movement, it must make several literacy programs in each region different because Indonesia is an autonomous country. To get around this, the government has made a legal umbrella and guidelines regarding the activities of the school literacy movement program. In implementing the school literacy movement, school principals have a very big share considering the government policy allows each school institution to develop programs that have been agreed upon by the government